Physiological changes in eucalyptus hybrids under different irrigation regimes - Valadares, Jane [UNESP]; Paula, Nádia Figueiredo De; Paula, Rinaldo Cesar De [UNESP] (Universidade Federal do Ceará, 2014)
With the expansion of the cultivation of eucalyptus into areas with limited water resources, recommending genotypes which are tolerant to low water availability is important in order to maximize productivity under such conditions. The aim of this work therefore was to evaluate five hybrids of Eucalyptus grandis x E. urophylla (H1 to H5) subjected to four irrigation regimes in the greenhouse: daily (IR1), every two days (IR2), every four days (IR4) and every six days (IR6). The following characteristics were evaluated: photosynthetic rate (A), transpiration (E), stomatal conductance (gs), leaf water potential (Ψw), leaf relative water content, photochemical efficiency and chlorophyll content index. Evaluations of A, gs and E were carried out on two occasions: 1 - under stress, at the end of the interval between irrigations for each treatment; and 2 - in recovery, 48 h after irrigation for all plants in the experiment. On average, there was reduction of 25 and 40% in A values, 40 and 55% in gs, 15 and 22% in E, and 96 and 103% in Ψw respectively in those plants under regimes IR4 and IR6, compared to under IR1. Stomatal conductance had only partially recovered 48 h after irrigation, and due to being more sensitive, its changes are a good indication of water stress. Hybrid H3 is the most tolerant and H5 the most sensitive to a reduction in water availability in soil.

Com a expansão da cultura do eucalipto para áreas com grandes limitações hídricas, torna-se importante a recomendação de genótipos tolerantes à baixa disponibilidade hídrica para a maximização da produtividade nestas condições. Assim, este trabalho objetivou avaliar cinco híbridos de Eucalyptus grandis x E. urophylla (H1 a H5) submetidos a quatro regimes de irrigação, em casa de vegetação: irrigação diária (RI1) e a cada dois (RI2), quatro (RI4) e seis dias (RI6). Avaliou-se a taxa fotossintética (A), transpiração (E), condutância estomática (g s), potencial hídrico (Ψw) e conteúdo relativo de água nas folhas, eficiência fotoquímica e índice de conteúdo de clorofila. As avaliações de A, g s e E foram realizadas em dois momentos: 1 - sob estresse: ao final do intervalo entre as irrigações de cada regime hídrico e 2 - sob recuperação: 48 h após a irrigação de todas as plantas do experimento. Em média, houve redução de 25 e 40% nos valores de A, de 40 e 55% em g s, de 15 e 22% em E e de 96 e 103% no Ψw, respectivamente, nas plantas submetidas aos regimes RI4 e RI6, comparativamente ao RI1. A condutância estomática recuperou-se apenas parcialmente, 48 h após a irrigação e, por apresentar-se mais sensível, suas alterações são boas sinalizadoras do estresse hídrico. O híbrido H3 é o mais tolerante e o H5 o mais sensível à redução da disponibilidade hídrica no solo.
Alterações fisiológicas em híbridos de eucalipto sob diferentes regimes de irrigação
Keywords: Water stress; Forest improvement; Physiological characteristics; Estresse hídrico; Melhoramento florestal; Características fisiológicas